A phase 1 study of ruxolitinib, steroids and lenalidomide for relapsed/refractory multiple myeloma patients. Issue 5 (14th August 2022) - Berenson, James R.; Kim, Clara; Bujarski, Sean; To, Jennifer; Spektor, Tanya M.; Martinez, Daisy; Turner, Carley; Ghermezi, Matthew; Eades, Benjamin M.; Swift, Regina A.; Schwartz, Gary; Eshaghian, Shahrooz; et al.
Abstract: Ruxolitinib with lenalidomide and dexamethasone shows anti‐myeloma effects in vitro and in vivo. MUC1 leads to lenalidomide resistance in multiple myeloma (MM) cells, and ruxolitinib blocks its expression. Thus, ruxolitinib may restore sensitivity to lenalidomide. A phase I trial was conducted to determine the safety and efficacy of ruxolitinib with lenalidomide and methylprednisolone for patients with relapsed/refractory (RR)MM who had been treated with lenalidomide, steroids and a proteasome inhibitor and showed progressive disease at study entry. A traditional 3 + 3 dose escalation design was used to enroll subjects in four cohorts. Subjects received ruxolitinib twice daily, lenalidomide daily on days 1–21 of a 28 day cycle and methylprednisolone orally every other day. Primary endpoints were safety, clinical benefit rate (CBR) and overall response rate (ORR). Forty‐nine patients were enrolled. The median age was 64 years and they had received a median of six prior treatments including lenalidomide and steroids to which 94% were refractory. No dose limiting toxicities occurred. The CBR and ORR were 49% and 36%, respectively. All responding patients were refractory to lenalidomide. Grade 3 or 4 adverse events (AEs) included anemia (17%), decreased lymphocyte count (15%), and hypophosphatemia (10%). Most common serious AEs included sepsis (9.8%) and pneumonia (7.8%). This Phase I trial demonstrates that a JAK inhibitor, ruxolitinib, can overcome refractoriness to lenalidomide and steroids for patients with RRMM. These results represent a promising novel therapeutic approach for treating MM. NCT03110822.